A Study on Effect of Process Parameters on Quality using Low Cost 3D Printer - N Aditya, T; Chandrakanth, A; Elangovan, M (International Journal of Engineering and Technology, 2018)
Fused deposition modeling is a type of layered additive manufacturing technology in which parts are built by heating a thermoplastic filament above its melting point. The modern low cost 3D printers are based on this technology. This paper examines the effect of process parameters on the quality of parts produced using ABS (Acrylonitrile-Butadiene Styrene) material. A statistical design of experiments approach, using the central composite design, was used with the process parameters of layer thickness, speed of deposition and extrusion temperature, to quantitatively model their effect on the quality of the resulting parts produced. It was found that layer thickness and speed of deposition had significant effect on quality of parts produced.Â Â